2008
DOI: 10.1177/0363546507313498
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Anterior Cruciate Ligament Reconstruction with Bone-Patellar Tendon-Bone Constructs

Abstract: Rupture of the anterior cruciate ligament is a common injury. Correct diagnosis and patient selection, along with proper surgical technique, with careful attention to anatomic graft placement, followed by attention to proper rehabilitation, leads to predictably good to excellent results. This article reviews the recognition and avoidance of complications associated with bone-patellar tendon-bone constructs of anterior cruciate ligament reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 104 publications
1
61
0
Order By: Relevance
“…However, there are drawbacks related to ACL reconstruction surgeries. [5][6][7] Recent studies have also shown that 70%-80% of the patients develop radiographic signs of osteoarthritis in the ACL reconstructed knee after 10 to 15 years. 8,9 Therefore, clinicians and researchers are aiming to improve the current treatment for ACL ruptures.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are drawbacks related to ACL reconstruction surgeries. [5][6][7] Recent studies have also shown that 70%-80% of the patients develop radiographic signs of osteoarthritis in the ACL reconstructed knee after 10 to 15 years. 8,9 Therefore, clinicians and researchers are aiming to improve the current treatment for ACL ruptures.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical reconstruction of the torn anterior cruciate ligament (ACL) is widely practiced, and can be performed using a number of potential grafts and surgical approaches (Busam et al, 2008;Sherman and Banffy, 2004). One of the most commonly used autografts is the bone-patellar tendon-bone (BPTB) graft, which has lead to very successful clinical outcomes and is widely regarded as the 'gold standard' in ACL reconstruction (Busam et al, 2008;Kapoor et al, 2004;Sherman and Banffy, 2004;Spindler et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most commonly used autografts is the bone-patellar tendon-bone (BPTB) graft, which has lead to very successful clinical outcomes and is widely regarded as the 'gold standard' in ACL reconstruction (Busam et al, 2008;Kapoor et al, 2004;Sherman and Banffy, 2004;Spindler et al, 2004). The BPTB graft typically involves removal of the central third from the patellar tendon.…”
Section: Introductionmentioning
confidence: 99%
“…A patellar tendon that is less than 25 mm in width may subject the patient to an iatrogenic patellar tendon rupture or extensor mechanism deficits after harvest. 6 Preoperative imaging that demonstrates notable degenerative changes of the patellofemoral joint (radiograph or magnetic resonance imaging [MRI]), findings of patellar tendonitis (MRI finding on the T2-sagittal image; calcification in the tendon), patella alta (Insall ratio > $1.2 to 1.4, resulting in a long tendon and potential mismatch), or findings of arthrofibrosis should also be closely scrutinized as to whether the patient is a candidate for BTB autograft reconstruction. 7 Once a decision is made to proceed with a BTB autograft, the patient should be made aware of not only the postoperative protocol (described later in the manuscript), but also the potential for postoperative effusion (which may necessitate drainage), harvest pain, swelling, and loss of range of motion.…”
Section: Patient Historymentioning
confidence: 99%